FOREIGN INVESTMENT AND DIPLOMACY - R. O. Raynkhardt (Vestnik MGIMO-Universiteta)
Book review: Oleg Pichkov, Evgeniy Rakov. Foreign Direct Investment and National Interest of the State. Moscow: MGIMO-University, 2016. 214 p.